Facile Fabrication of Hybrid Perovskite Single‐Crystalline Photocathode for Photoelectrochemical Water Splitting. Issue 5 (9th April 2021) - Zhang, Xingmo; Zhang, Rui; Yang, Tiebin; Cheng, Yahui; Li, Feng; Li, Wenxian; Huang, Jun; Liu, Hui; Zheng, Rongkun
Abstract : Recently, beyond various optoelectronic devices, lead halide perovskites have emerged as promising candidates for high‐performance photocatalysts owing to their excellent optoelectronic properties. However, most previous works on perovskite photocatalysts mainly used the forms of nanocrystals that need the perovskite‐saturated electrolyte or polycrystalline thin films that still suffer from the instability in water and low performance. Herein, the synthesis of high‐quality hybrid perovskite single crystals and their implementation as photocathodes for water splitting with a simple device structure are reported on. Optimized perovskite crystals exhibit a good water splitting photocurrent density of −0.51 mA cm −2 at 0 V versus reversible hydrogen electrode (RHE) under visible light illumination. Moreover, such devices as the p‐type photocathodes show improved stability, exhibiting no obvious decrease over 600 s. This work highlights the great potential of hybrid perovskite single crystals for photocatalyst applications in aqueous solution. Abstract : A hybrid perovskite single‐crystal photocatalyst device is fabricated with a facile device architecture of fluorine‐doped tin oxide (FTO)/Ag/CH3 NH3 PbBr3 . The stable and high device performance of the as‐prepared p‐type photocathode exploits the great potential of perovskite single crystals for water splitting applications.